Modernity and Identity in Oraman Village Architecture of the West of Iran - Jooshesh, Mohammad; Kolahi, Negar; Jafar Khazaee, Mohammad (Nakhara : Journal of Environmental Design and Planning, 2011)
In Kurdistan, Kermanshah and West Azerbaijan provinces of Iran, there are regions with plain but amazing contexts by which one can identify the hidden identity of the regional architecture in its various components. Most villages are built on the sides of narrow valleys with over a 50° slope. They face south and southeast to receive the most daylight. In the fi rst part of this article the topographic and architectural structure of the region is introduced, and in the second part, specific sections of this region have been analyzed in terms of modernity in relation to the hidden identity of the traditional architecture, urban planning and the components of forming spaces. In addition, fundamental similarities of this vernacular architecture and precepts of the International Style have been compared in the fi nal part, in order to explore the possibility of creating a distinctive form of modernity within the hidden identity of Oraman Village architecture.